Valorization of Food Loss and Wastes: Feedstocks for Biofuels and Valuable Chemicals - Isah, Shehu; Ozbay, Gulnihal (Frontiers in Sustainable Food Systems, 2020)
Reduction in the amount of food loss and waste requires appropriate quantification method of the amount of food loss annually on the one hand and devising alternative use for foods that would otherwise end up as loss or waste. In this review, food loss and waste (FLW)were classified as avoidable, nonavoidable and possibly avoidable wastes based on inherent composition of several food categories. The current disposal methods of FLW were evaluated for its effectiveness and overall environmental impacts presented by landfills, composting and incineration. Alternative and sustainable alternative for management of food loss and waste include feedstocks for biofuel production, valuable chemicals and coproducts. This approach is renewable, environmentally friendly, improved social status through job creation for local communities and overall improved quality of life.